Respuesta :
Answer:
I think is c -2.
y=3x+6
2x+4y=−4
y = 5x + 4y - 4
-4y - 4y
5x- 4y = -4 -4y
Answer:y = 0
Step-by-step explanation:
The given system of linear equations is expressed as
y = 3x + 6
3x - y = - 6- - - - - - - - - - - - -1
2x + 4y = - 4- - - - - - - - - - - -2
We would eliminate x by multiplying equation 1 by 2 and equation 2 by 3. It becomes
6x - 2y = - 12- - - - - - - - - - -3
6x + 12y = - 12- - - - - - - - - - - -4
Subtracting equation 4 from equation 3, it becomes
- 14y = 0
y = 0
Substituting y = 0 into equation 1, it becomes
3x - 0 = - 6
3x = - 6
Dividing the left hand side and the right hand side of the equation by 3, it becomes
3x/3 = - 6/3
x = - 2